Association of Maternal First-trimester Ondansetron Use With Cardiac Malformations and Oral Clefts in Offspring. Issue 3 (September 2019) - Huybrechts, K.F.; Hernández-Díaz, S.; Straub, L.; Gray, K.J.; Zhu, Y.; Patorno, E.; Desai, R.J.; Mogun, H.; Bateman, B.T.
Abstract : ( JAMA . 2018;320(23):2429–2437) Ondansetron, a 5-HT3 receptor antagonist, has become the most frequently prescribed drug for nausea and vomiting during pregnancy. However, this medication is not formally approved for this use, and available evidence regarding ondansetron and fetal safety is limited or conflicting. The American College of Obstetricians and Gynecologists has concluded that further studies are warranted. Therefore, the authors of the present study investigated potential associations between ondansetron exposure during the first trimester of pregnancy and the risk of cardiac malformations and/or oral clefts in neonates.